Spatial analysis of income inequality: the case of Sumatra Island, Indonesia - Arif Rahman,; Inggrita Gusti Sari Nasution,; Raina Linda Sari,; Irsad Lubis,; Sirojuzilam,; Wahyu Ario Pratomo, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aims to examine the convergence of income inequality (Gini) and to investigate its determinants and spillover effects. This study used panel data from 10 provinces in Sumatra Island, Indonesia, spanning the years 2015-2022, sourced from the Statistics Indonesia and the Indonesian Ministry of Environment and Forestry. The Generalized Method of Moment was utilised to analyse the occurrence of convergence, while the Spatial Autoregressive model with Autoregressive Disturbances model was used to examine its direct effects and spillover effects. The results indicate that there is convergence in income inequality across provinces. Environmental quality, per capita income, and democracy directly reduce income inequality, whereas the industrial sector exacerbates it. There is a strong spillover effect whereby an increase in real per capita income of the observed province reduces inequality in neighbouring provinces. However, the expansion of the industrial sector across regions further increases inequality. Additionally, environmental quality, industry, and democracy do not have significant spillover effects. The study discovered convergence of income inequality (Gini) across provinces. We adopted the spatial econometric methods at the island scale, which have not previously been used in the Indonesian context. It also contributes to understanding the direct effects of democracy, environment, industry, and spillover effects of real income per capita on income inequality. The convergence results imply a process towards equilibrium in the performance of the determinant variables in each province. The spillover effect of real GRDP per capita highlights the role of the central government in strengthening inter-regional connectivity in Sumatra. Provincial governments play a role in providing direct effects that further strengthen democracy, environment, and income, as well as addressing ongoing industrial policies. Prudence in promoting growth needs to be pursued to ensure that the small industry sector can advance and contribute to broader equity, without compromising the environment.